1982
DOI: 10.1128/iai.37.3.875-883.1982
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical characterization of extracellular proteases from Vibrio cholerae

Abstract: Isoelectric focusing of culture supernatants from Vibrio cholerae El Tor 1621 and high protease-producing mutant strain 1621 hip revealed the presence of three different types of extracellular protease. Type I protease was the major activity in the wild-type strain and was inhibited by phenylmethylsulfonyl fluoride and by the lima bean trypsin inhibitor. Type II protease was present in the wild type and was the major activity in the high protease-producing mutant. It was resistant to inhibitors of metalloprote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

1985
1985
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…proteins demonstrated proteolytic activity and were antigenically indistinguishable. Possession of multiple enzyme forms, as observed here, is a common feature among zinccontaining proteases from other bacterial species (9,11,27) and other enzymes in general (19). The molecular microheterogeneity observed following electrophoresis could be a consequence of single amino acid residue changes (5), posttranslational covalent modifications, autodigestion (9), or modification occurring as a result of purification (19).…”
Section: Discussionmentioning
confidence: 65%
“…proteins demonstrated proteolytic activity and were antigenically indistinguishable. Possession of multiple enzyme forms, as observed here, is a common feature among zinccontaining proteases from other bacterial species (9,11,27) and other enzymes in general (19). The molecular microheterogeneity observed following electrophoresis could be a consequence of single amino acid residue changes (5), posttranslational covalent modifications, autodigestion (9), or modification occurring as a result of purification (19).…”
Section: Discussionmentioning
confidence: 65%
“…During the course of these experiments, we observed that SDS-PAGE analysis of V. cholerae outer membrane proteins revealed marked degradation of many proteins in lysates of the wildtype strain but not in lysates prepared with the rpoS::cm mutant. We reasoned that the rpoS mutation may have affected either the secretion or production of one or more of the previously described V. cholerae O1 proteases (55). This possibility was examined by measuring the protease activity secreted into culture supernatants by the wild-type strain, the rpoS::cm mutant, and the mutant with complementing plasmids.…”
Section: Figmentioning
confidence: 99%
“…Protease-deficient mutants are known to be less virulent [1]. Young and Broadbent reported the purification of three types of protease from V. cholerae O1: phenylmethylsulfonyl fluoride inhibitable type 1, metalloprotease and serine protease inhibitor resistant type II, and EDTA inhibitable type III [2]. Booth et al [3,4] reported that soluble HA/protease is a metalloenzyme that can be inhibited by a variety of chelating agents and inhibitors of zinc * Corresponding author.…”
Section: Introductionmentioning
confidence: 99%